2019
DOI: 10.1021/acs.inorgchem.9b01959
|View full text |Cite
|
Sign up to set email alerts
|

An Anionic Nanotubular Metal–Organic Framework for High-Capacity Dye Adsorption and Dye Degradation in Darkness

Abstract: A metal−organic framework (MOF), named SCNU-Z2, based on a new heterotopic tripodal nitrogen-containing ligand, has been constructed. Due to the replacement of one imidazole group in the reported ligand with one tetrazole group, the charge of the framework is changed from cationic to anionic but retains the same framework structure. The framework consists of tubular channels with a diameter of 1.5 nm and exhibits satisfactory stability in water with a pH range of 3−11. The anionic nature of the framework allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…Even under the dark condition, the sulfurized NRs exhibit a 35.7% degradation rate within 40 min. The dye degradation in the dark was reported previously for Cu2−xS nanocrystals [37], and this may be due to a self-cyclic redox reaction of multivalent copper [18,26], or a low-temperature, thermocatalytic reaction in the dark system [38]. On the other hand, natural light can improve the degradation rate to 51.5% at 40 The two stages are supposedly related to the dye adso process [11] and photocatalytic degradation reaction [39].…”
Section: Resultsmentioning
confidence: 60%
“…Even under the dark condition, the sulfurized NRs exhibit a 35.7% degradation rate within 40 min. The dye degradation in the dark was reported previously for Cu2−xS nanocrystals [37], and this may be due to a self-cyclic redox reaction of multivalent copper [18,26], or a low-temperature, thermocatalytic reaction in the dark system [38]. On the other hand, natural light can improve the degradation rate to 51.5% at 40 The two stages are supposedly related to the dye adso process [11] and photocatalytic degradation reaction [39].…”
Section: Resultsmentioning
confidence: 60%
“…Such a change maybe from the π–π interactions between the channel wall and the conjugate planes of MB molecules. 47 Moreover, the two adsorption bands for MB⊂VNU-23 centered at 1135 and 1176 cm −1 correspond to the sulfonic groups' vibrational modes. These bands display a shift to the lower frequency in comparison with the original peaks of the sulfonic groups within VNU-23, which suggests that the mechanism of adsorption of MB onto VNU-23 includes electrostatic interactions between the SO 3 − groups and MB + .…”
Section: Resultsmentioning
confidence: 98%
“…118 Zheng and coworkers have prepared and characterised SCNU-Zl-Cl, and used it for the removal of anionic pollutants like MO, acid orange A, CR and MB with an adsorption efficiency of 285 mg g À1 , 180 mg g À1 , 585 mg g À1 , and 262 mg g À1 , respectively. 119 Vafaei et al prepared a cadmium based MOF (Cd-ZIF) for MG removal from dye contaminated wastewater. They reported that its adsorption capacity is higher than POM@UiO-66, which is also used for removal of MG. Cd-ZIF has shown an adsorption capacity of 395.87 mg g À1 while that shown by POM@UiO-66 is 190.6 mg g À1 .…”
Section: Adsorption Through Mofsmentioning
confidence: 99%
“…122,123 The MOF composites (SCNU-Z2, SCNU-Z1-Cl, Th-TATAB, and CAU-1) have demonstrated higher removal capacity for organic dyes from water. 119,124,125 Recent results show that ZJU-48 and {[Zn 4 (bpndc) 4 (b2mpm) 2 ]Á2DMFÁ 4H 2 O} can also be good adsorbents for various dyes (MO, RhB, MB, and NR) with high removal capacity. 126,127 Shahid et al have developed a copper-based MOF [{Cu (bipy) 1.5 (H 2 -pdm)}Á2NO 3 ÁH 2 O] n (Cu-MOF-1) for the adsorptive removal of MB, MO and RhB from wastewater effluents.…”
Section: Adsorption Through Mofsmentioning
confidence: 99%